Atmospheric corrosion map for service life prediction of lattice steel tower using air pollution data and meteorological data - Usman F.; Khalid N.H.N.; Omar R.C.; Jawas M.J.A. (American Institute of Physics Inc., 2023)
Air pollution-induced deterioration of metallic components in infrastructures. An overhead transmission tower is among the strategic asset that belongs to the nation. Tenaga Nasional Berhad is the primary energy utility company in Malaysia who has owned and maintained the national grid system. It carries more than 23,000 circuit kilometers, which comprised of 500 kV, 275 kV, and 127 kV electric transmission lines all over Peninsular Malaysia. Electric transmission towers that function to support the transmission line are mostly a lattice steel type of structure. The structural trusses comprised of different sizes, equal sections, plates, and connected using a bolted connection. Tremendous industrial development nowadays has become an issue for the environment, especially air pollution. The combination of atmospheric corrosive agents with the climate condition has caused corrosion to the metallic structure. This paper presents the development of a corrosion hazard map using geospatial analysis for ten years of air pollutant concentration, from wet deposition data of nitrate, sulfate, and chloride in the atmosphere. The meteorological data, which are temperature, humidity, received rainfall, and time of wetness, was considered in the analysis as well. By applying the inverse distance weighted interpolation method, the corrosion hazard map determined from this study was classified into five zones of corrosion hazard. The study discovered that the southern area of Peninsular Malaysia, which is from Johor, Melaka to Selangor have the highest level of corrosion hazard due to the atmospheric corrosion. The corrosion hazard map determined from this study could be used as a reference on the level of corrosion hazard for engineering development and maintenance purposes. Moreover, it also can accommodate engineers or designers in selecting a proper coating for corrosion mitigation and as a justification for coating specification, either in engineering or automotive field. 2021 American Institute of Physics Inc.. All rights reserved.